Swimming Across the World: The Portrayal of Mermaid in Mermaid and Swordsman, The Little Mermaid Live Action and Mermaid in Love 2 Dunia - Cahya, Silviana Lintang; Ilmi, Afwi Madinatul; Nuraini, Desvita; Wulandari, Dyah Uyun; Aminah, Qirara Azamatul; Purmitasari, Rani Pradiva (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2025)
Mermaids are one of the most popular mythological creatures and are often discussed today. It's no wonder that nowadays, mermaids are featured in various media, including films. More interestingly, it turns out that each culture has a different interpretation of mermaids, especially their portrayal. This research explores the portrayal of mermaids in three cultural contexts depicted in the films Mermaid and Swordsman (China), The Little Mermaid Live Action (Denmark), and Mermaid in Love 2 Dunia (Indonesia). Using Hayward's (2018) theoretical framework, this analysis categorises these representations into 2 framework perspectives: syncretic and mermaidisation, highlighting cultural integration and transformation in their depiction. The results show that Chinese mermaids combine elements of traditional mythology with cultural motifs, such as traditional hanfu clothing. In Denmark, mermaid depictions blend classical folklore and modern interpretations of values. Meanwhile, mermaids in Indonesia feature innovative elements, such as an upright swimming style and the integration of local fish motifs that reflect the archipelago's distinctive cultural adaptations. By analysing representation in narratives of various cultures, this research contributes to understanding how cultural adaptation is depicted in the representation of mythological creatures, such as mermaids. In addition, this research also provides insights for future interdisciplinary studies on how mermaids are portrayed in various cultures in popular media such as film, mythology, and cultural studies.